1997
DOI: 10.1038/sj.leu.2400575
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of differentiation, clonal proliferation, cell cycle progression and bcl-2 expression in RARα-altered sublines of HL-60

Abstract: All-trans retinoic acid (RA) induces granulocytic differentiationbind all-trans RA as well as 9-cis RA, while RXRs bind only of acute promyelocytic leukemia cells both in vivo and in vitro.9-cis RA. [19][20][21] Thus, RARs heterodimerize to form RAR/RXR sociated from induction of differentiation and/or apoptosis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Several studies suggested that growth inhibition by 1,25(OH) 2 D 3 may be attributed to inhibition of the G 1 to S transition in the cell cycle, which probably is due at least in part to stimulation of expression of the cyclin-dependent kinase inhibitors (CDKIs), p21 waf1 and p27 kip1 as well as induction of programmed cell death. [1][2][3][4] In a clinical study, oral administration of 1,25(OH) 2 D 3 to preleukemic patients was only partially effective 5 ; calcemic side effects prevented the administration of the dosage of the compound needed to achieve the concentration of 1,25(OH) 2 D 3 in vivo, which was known to be necessary from our in vitro studies. 5,6 Therefore, synthesis of vitamin D 3 analogs with potent antiproliferative and differentiation activity against cancer cells with decreased risk of hypercalcemia has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that growth inhibition by 1,25(OH) 2 D 3 may be attributed to inhibition of the G 1 to S transition in the cell cycle, which probably is due at least in part to stimulation of expression of the cyclin-dependent kinase inhibitors (CDKIs), p21 waf1 and p27 kip1 as well as induction of programmed cell death. [1][2][3][4] In a clinical study, oral administration of 1,25(OH) 2 D 3 to preleukemic patients was only partially effective 5 ; calcemic side effects prevented the administration of the dosage of the compound needed to achieve the concentration of 1,25(OH) 2 D 3 in vivo, which was known to be necessary from our in vitro studies. 5,6 Therefore, synthesis of vitamin D 3 analogs with potent antiproliferative and differentiation activity against cancer cells with decreased risk of hypercalcemia has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,11,[20][21][22] However, one drug resistant HL60 subline underwent differentiation without loss of bcl-2 protein 31 and transfection of bcl-2 does not inhibit differentiation. 19 Using flow cytometric protein measurement in conjunction with cell cycle analysis, we were able to examine protein expression on G0/G1 cells, thus ruling out the generalised protein loss of cell decay.…”
Section: Figurementioning
confidence: 99%
“…Ligation of this receptor is known to induce differentiation in leukemic cell lines. 6 In combination with other agents ATRA has also been found to inhibit the growth of non-APL (non-M3) AML blasts in vitro. 7,8 A number of retinoid and vitamin D analogues have been synthesized in recent years in the search for compounds which target malignant cell differentiation and apoptosis with minimal toxic effects on other systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 is normally expressed in human B lymphocytes, 26 but physiological expression is not restricted to B cells because hematopoietic precursors of all lineages express bcl-2. Independent of t(14;18) translocation bcl-2 dysregulation has been observed in several hematologic malignancies, such as chronic lymphoblastic leukemia, 27 acute myelogenous leukemia, [28][29][30][31][32][33][34][35] acute lymphoblastic leukemia and [36][37][38] lymphomas. [39][40][41] The common element of bcl-2 family members is amino acid homologies in the binding domains BH1 and BH2.…”
Section: Introductionmentioning
confidence: 99%